2002
DOI: 10.1038/sj.cgt.7700468
|View full text |Cite
|
Sign up to set email alerts
|

Selective killing of cancer cells based on translational control of a suicide gene

Abstract: The translation initiation factor, eIF4E, is commonly overexpressed in solid tumors. This elevation allows for efficient translation of mRNA that are normally repressed by their 5 0 untranslated region, many of which encode growth -promoting proteins. This property was exploited to modulate the synthesis of HTK at the translational level to selectively kill cancer cells. Various breast cancer cell lines can efficiently synthesize HTK from the translationally regulated mRNA, whereas normal cells cannot. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 27 publications
0
44
0
Order By: Relevance
“…Systemic administration of the prodrug gancyclovir would then be expected to be benign in normal tissues, but converted into its toxic phosphorylated product only in tumor cells. This concept was demonstrated using the 5 0 UTR of rat FGF2 (619 bases, stability of À55 kcal/mol) upstream of the gancyclovir open reading frame (DeFatta et al, 2002). These experiments demonstrated that tumor cells expressing the chimeric HSV-TK RNA could be killed at up to 500-fold lower concentrations of gancyclovir than normal cells, in a manner that was dependent on eIF4E expression (DeFatta et al, 2002).…”
Section: Selective Translational Expression Of Killer Genes In Tumor mentioning
confidence: 89%
See 1 more Smart Citation
“…Systemic administration of the prodrug gancyclovir would then be expected to be benign in normal tissues, but converted into its toxic phosphorylated product only in tumor cells. This concept was demonstrated using the 5 0 UTR of rat FGF2 (619 bases, stability of À55 kcal/mol) upstream of the gancyclovir open reading frame (DeFatta et al, 2002). These experiments demonstrated that tumor cells expressing the chimeric HSV-TK RNA could be killed at up to 500-fold lower concentrations of gancyclovir than normal cells, in a manner that was dependent on eIF4E expression (DeFatta et al, 2002).…”
Section: Selective Translational Expression Of Killer Genes In Tumor mentioning
confidence: 89%
“…This concept was demonstrated using the 5 0 UTR of rat FGF2 (619 bases, stability of À55 kcal/mol) upstream of the gancyclovir open reading frame (DeFatta et al, 2002). These experiments demonstrated that tumor cells expressing the chimeric HSV-TK RNA could be killed at up to 500-fold lower concentrations of gancyclovir than normal cells, in a manner that was dependent on eIF4E expression (DeFatta et al, 2002). This concept was extended by using either a lentivirus or adenovirus (Mathis et al, 2006) to deliver such constructs, as well as adding a prostate specific promoter to drive expression specifically in prostate epithelial cells .…”
Section: Selective Translational Expression Of Killer Genes In Tumor mentioning
confidence: 99%
“…eIF4E should also prove to be central to our understanding of P-bodies and mRNA degradation because P-bodies lack ribosomes and all translation initiation factors except eIF4E (37). The involvement of eIF4E in malignant transformation and metastasis is the subject of intense research (38), including its utility as a marker for cancer stage and potential to serve as a target for novel anticancer therapies (39,40). Further knowledge of the factors that influence eIF4E function should aid in our understanding of malignant transformation and in the development of therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 Previous studies have illustrated an increase of the intrinsic levels eIF4E in a variety of malignancies, including prostate cancer. 4 Elevations in eIF4E lead to increases in cell proliferation, suppression of apoptosis and other characteristics associated with neoplastic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…13 The 5 0 UTRs from FGF-2 and ODC have previously been shown to contain extensive, stable secondary structures, and it has previously been reported that their translation is tightly controlled. 10,13,14 We found that two out of the three 5 0 UTR tested in vitro showed excellent potential for tumor-specific targeting based on eIF4E levels and the extent of enhanced green fluorescent protein (GFP) expression. Infection of prostate tumors in the PTEN À/À transgenic mouse model confirmed this impression.…”
Section: Introductionmentioning
confidence: 99%